Case study: the use of smartphone application technology to improve dietary practices, nutrition knowledge and body composition of a female international rugby union player - Curtis, C.; Russell, M.; Ranchordas, M. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Nutrition application (app) technology may offer a cost-effective and novel method of maintaining better communication between athletes and practitioners at times of the season when such interactions may be limited (i.e. periods separating livein training camps). In contrast to clinical populations, limited research has profiled the use of nutrition app technology within athletic cohorts. With indices of nutrition knowledge, body composition and dietary intake of primary interest, this case study reports the effects of implementing nutrition app usage with a female international rugby union player (19 years old, 6 international U20s caps). Anthropometric data, a general nutrition knowledge questionnaire (GKNQ) and a 3-day food diary were collected before and after an 8-week in-season period that separated two consecutive training camps. Normal communication methods between camps were complemented by the use of app technology (MealLogger, New York) which allowed photo and text commentary interactions between the athlete and performance nutritionist. Daily energy intake increased (2029 kCal.d-1 to 2213 kCal.d-1), GKNQ scores improved (68 to 76; +11%) and body composition benefitted (8-site skinfold sum 133mm to 112mm) from the 8-week period that required the upload, and subsequent commentary on, 161 meal photographs (~2.8 meals a day). By means of comparison, such changes were not observed in a comparable control player who completed the 8 week programme but did not receive the additional support via nutrition app technology. In scenarios where athlete-practitioner communication may be limited, the use of a nutrition app may be of benefit to the performance nutritionist to increase nutrition knowledge and body composition in team sport players.